Touch conductive film and preparation method, electronic device, conductive ink and preparation method

By using silver ion source materials, polyvinylpyrrolidone and thiol compounds and other materials in the preparation of the touch conductive film, silver nanowire conductive ink with titanium dioxide wrapped at the end is formed. Combined with the surface dry treatment and hot pressing treatment, the problems of cumbersome and high cost of touch conductive film preparation in the prior art are solved, and an efficient and reliable one-step molding process is achieved.

CN119356550BActive Publication Date: 2025-04-25ZHEJIANG DAHUA TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411923130.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-25
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

In the prior art, the touch conductive film cannot be formed in one step, and the preparation steps are cumbersome and costly.

Method used

The silver ion source material and polyvinylpyrrolidone react in a polyol to form a first mixed solution, and mixed it with a second mixed solution containing a sulfhydryl group, and added carboxy-modified titanium dioxide microspheres. After treatment, the silver nanowires wrapped with titanium dioxide at the end were separated, and dispersed into the acrylic solution to form conductive ink, coated on a transparent substrate for surface drying and hot pressing treatment to form a conductive area and an insulating area.

Benefits of technology

One-step molding of the touch conductive film is realized, the preparation process is simplified, the preparation efficiency and reliability are improved, and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119356550B_ABST
    Figure CN119356550B_ABST
Patent Text Reader

Abstract

The present application discloses a touch conductive film and a preparation method, an electronic device, a conductive ink and a preparation method. The preparation method of the touch conductive film includes: dissolving a silver ion source material and PVP in a polyol to react to form a first mixed solution; adding a second mixed solution containing a thiol group to obtain a third mixed solution; then adding carboxyl-modified titanium dioxide microspheres to obtain a fourth mixed solution; treating the fourth mixed solution to separate silver nanowires with titanium dioxide wrapped at the ends; dispersing the silver nanowires with titanium dioxide wrapped at the ends into an acrylic acid solution to obtain a conductive ink; coating the conductive ink on the surface of a transparent substrate and performing a surface drying treatment to obtain a first substrate; performing a hot pressing treatment on a preset area of ​​the first substrate to obtain a conductive area; baking and curing the area outside the conductive area to obtain a touch conductive film. The present application can obtain a touch conductive film by one-step molding through a wet process, with high preparation efficiency, simple preparation process, high reliability and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of touch screen technology, and in particular to a touch conductive film and a preparation method thereof, an electronic device, and a conductive ink and a preparation method thereof. Background Art

[0002] Silver nanowire touch electrodes and indium tin oxide touch electrodes are currently commonly used sensing electrode materials in the touch field. However, the scarcity of indium (In) sources, toxicity, complex processes and high costs, low photoelectric performance and inherent brittleness have severely restricted the development of indium tin oxide (ITO). Theoretically, silver nanowire touch electrodes can be obtained through a wet process, while indium tin oxide touch electrodes are obtained through a physical vapor deposition (PVD) process. The overall process difference is large, resulting in a significant overall cost gap, especially when used in large-size fields. In addition, due to the resolution problem of the existing coating process, it is impossible to achieve one-step electrode forming. It is necessary to dry or wet etch the array electrode after full-plate coating, which cannot highlight the advantages of the wet process compared to ITO full-plate magnetron sputtering, resulting in no theoretical gap in cost compared to ITO. At the same time, there will be a cross-section after laser etching, which will affect the bonding effect and make it easy for water vapor to enter. After laser etching, the subsequent entry of water vapor will cause the nanosilver to appear yellow along the laser line, affecting the overall appearance of the product. Summary of the invention

[0003] The present application provides a touch conductive film and a preparation method, an electronic device, a conductive ink and a preparation method, so as to solve the problems in the prior art that the touch conductive film cannot be formed in one step, the preparation steps are complicated and the cost is high.

[0004] A first aspect of an embodiment of the present application provides a method for preparing a touch conductive film, the method comprising: dissolving a silver ion source material and polyvinyl pyrrolidone (PVP) in a polyol to react to form a first mixed solution; providing a second mixed solution containing a thiol group; mixing the first mixed solution and the second mixed solution to obtain a third mixed solution; adding carboxyl-modified titanium dioxide microspheres to the third mixed solution to obtain a fourth mixed solution; treating the fourth mixed solution to separate silver nanowires with titanium dioxide wrapped at the ends; dispersing the silver nanowires with titanium dioxide wrapped at the ends into an acrylic acid solution to obtain a conductive ink; coating the conductive ink on the surface of a transparent substrate and performing a surface drying treatment to obtain a first substrate; performing a hot pressing treatment on a preset area of ​​the first substrate to obtain a conductive area; and baking and curing the area outside the conductive area to obtain a touch conductive film.

[0005] According to one embodiment of the present application, the first mixed liquid includes a first intermediate product, which is a silver nanowire wrapped with polyvinyl pyrrolidone along the length direction, and the diameter of the first intermediate product is 20nm~50nm.

[0006] According to one embodiment of the present application, in the step of dissolving the silver ion source material and polyvinyl pyrrolidone (PVP) in a polyol to react and form a first mixed solution, at least one of the following conditions is met: (1) the mass ratio of the silver ion source material to the polyvinyl pyrrolidone is 1:0.6~1:1.2; (2) the silver ion source material includes at least one of silver nitrate, silver acetate, silver fluoride and silver perchlorate; (3) according to one embodiment of the present application, the molecular weight range of polyvinyl pyrrolidone is 36000~50000; (4) the polyol includes at least one of ethylene glycol, 1,2-propylene glycol or glycerol.

[0007] According to one embodiment of the present application, the step of providing a second mixed solution containing thiol groups includes: adding a thiol compound to an alkaline solution and adjusting the pH value to between 7.0 and 9.0 to obtain a second mixed solution containing thiol groups.

[0008] According to one embodiment of the present application, the alkaline solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution; and / or the thiol compound includes at least one of thioglycolic acid, mercaptopropionic acid, 2-mercaptopropane, cysteine, mercaptoethylamine, 3-mercapto-1-propylamine, and 4-amino-2-mercaptopyrimidine.

[0009] According to one embodiment of the present application, in the step of mixing the first mixed solution and the second mixed solution to obtain the third mixed solution, the mass ratio of the silver ion source material to the thiol compound in the second mixed solution containing thiol groups is 1:1~1:5.

[0010] According to one embodiment of the present application, in the step of mixing the first mixed liquid and the second mixed liquid to obtain the third mixed liquid, the stirring time is 30 min to 90 min; in the step of adding carboxyl-modified titanium dioxide microspheres to the third mixed liquid to obtain the fourth mixed liquid, the stirring time is 30 min to 120 min; the step of processing the fourth mixed liquid to separate the silver nanowires with titanium dioxide wrapped at the ends includes: centrifuging the fourth mixed liquid, washing with water, and dispersing it.

[0011] According to one embodiment of the present application, in the step of adding carboxyl-modified titanium dioxide microspheres to the third mixed solution to obtain the fourth mixed solution, the mass ratio of the carboxyl-modified titanium dioxide microspheres to the thiol compound is 1:0.1~1:1.

[0012] According to one embodiment of the present application, in the step of dispersing silver nanowires with titanium dioxide wrapped at the ends into an acrylic solution to obtain a conductive ink, the mass of the silver nanowires with titanium dioxide wrapped at the ends is 0.1% to 10% of the mass of the acrylic solution.

[0013] According to one embodiment of the present application, in the step of coating the conductive ink on the surface of the transparent substrate and performing surface drying treatment to obtain the first substrate, the thickness of the wet film formed by the conductive ink on the surface of the transparent substrate is 80nm~200nm, and the temperature of the surface drying treatment is 45℃~65℃.

[0014] According to one embodiment of the present application, in the step of performing hot pressing treatment on a preset area of ​​the first substrate to obtain a conductive area, the temperature of the hot pressing treatment is 160° C. to 220° C. and the pressure is 0.2 MPa to 1 MPa.

[0015] According to an embodiment of the present application, in the step of baking and curing the area outside the conductive area to obtain the touch conductive film, the baking temperature is 100° C. to 150° C.

[0016] A second aspect of an embodiment of the present application provides a touch conductive film, which is prepared by any of the above-mentioned methods for preparing a touch conductive film; the touch conductive film includes a silver nanowire core-shell composite material, and the silver nanowire core-shell composite material includes silver nanowires with ends wrapped with titanium dioxide or partially wrapped with ends.

[0017] According to a third aspect of an embodiment of the present application, there is provided an electronic device, the electronic device comprising a touch control component, and the touch control component comprises the touch control conductive film as described above.

[0018] A fourth aspect of an embodiment of the present application provides a conductive ink, which includes an acrylic solution in which silver nanowires having ends coated with titanium dioxide are dispersed.

[0019] A fifth aspect of an embodiment of the present application provides a method for preparing a conductive ink, comprising dissolving a silver ion source material and polyvinyl pyrrolidone (PVP) in a polyol to react and form a first mixed solution; providing a second mixed solution containing a thiol group; mixing the first mixed solution and the second mixed solution to obtain a third mixed solution; adding carboxyl-modified titanium dioxide microspheres to the third mixed solution to obtain a fourth mixed solution; treating the fourth mixed solution to separate silver nanowires with titanium dioxide wrapped at the ends; and dispersing the silver nanowires with titanium dioxide wrapped at the ends in an acrylic acid solution to obtain a conductive ink.

[0020] The beneficial effect is as follows: the present application directly coats the conductive ink prepared by the method of the present application on the surface of a transparent substrate, and after surface drying, the preset area is subjected to hot pressing treatment, so that the core-shell structure at the end of the silver nanowire is broken by high temperature and high pressure, thereby forming a conductive area, i.e., a touch electrode; the non-conductive area is directly baked and cured at a relatively low temperature to form an insulating area. The touch electrode and the insulating area together constitute a touch conductive film. The present application can obtain a touch conductive film by a one-step molding method using a wet process, which has high preparation efficiency, simple preparation process, high reliability, and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which:

[0022] Figure 1 It is a schematic diagram of the process of preparing the touch conductive film of the present application;

[0023] Figure 2 This is a schematic diagram of the growth of silver nanowires in the present application;

[0024] Figure 3 is a schematic diagram of the structure of the second intermediate product of the present application;

[0025] Figure 4 It is a structural schematic diagram of the electronic device of the present application. DETAILED DESCRIPTION

[0026] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0028] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0029] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0030] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0031] The current method of preparing touch capacitive screens cannot achieve one-step electrode forming due to the accuracy issues of the existing coating process. It requires full-plate coating and then dry or wet etching of the array electrodes. Compared with ITO full-plate magnetron sputtering, it cannot highlight the advantages of the wet process, resulting in no theoretical difference in cost compared to ITO.

[0032] Therefore, the present application provides a method for preparing a touch conductive film, referring to Figure 1 , the method comprises the following steps:

[0033] S110: dissolving the silver ion source material and polyvinyl pyrrolidone (PVP) in polyol to react and form a first mixed solution.

[0034] The first mixed solution includes a first intermediate product, and the first intermediate product is a silver nanowire wrapped with polyvinyl pyrrolidone (PVP) along the length direction.

[0035] Specifically, refer to Figure 2 , Figure 2 Schematic diagram of the growth of silver nanowires. The {100} crystal plane is the length direction of the silver nanowire, and the {111} crystal plane is the diameter direction of the silver nanowire. Compared with the {111} crystal plane of silver, polyvinyl pyrrolidone (PVP) has a greater affinity for the {100} crystal plane of silver. Therefore, polyvinyl pyrrolidone (PVP) is wrapped on the {100} crystal plane and hinders the deposition of silver atoms on the {100} crystal plane, thereby causing the seed to grow toward the {111} crystal plane. The growth of silver nanowires will go through three stages, namely the pre-nucleation stage, the nucleation stage, and the growth stage. First, under certain conditions, the silver ions in the silver ion source material are reduced to silver atoms by the reducing agent. As the reaction proceeds, the concentration of silver atoms will continue to increase until it reaches the critical value of nucleation. This process is the pre-nucleation stage. When the concentration of silver atoms reaches a concentration that can nucleate, they quickly aggregate into clusters to nucleate. The reaction enters the explosive nucleation stage from the pre-nucleation stage. This period of time is the nucleation stage, and the process is relatively short. When the nuclei grow to a critical size, they gather together to form seed crystals. Finally, under the action of the structure inducing agent, the seed crystals that continuously adsorb silver atoms gradually grow along the {111} crystal plane to form one-dimensional silver nanowires. Among them, polyvinyl pyrrolidone (PVP) not only acts as a stabilizer to prevent the agglomeration of silver nanoparticles, but also promotes the formation and growth of silver nanowires by interacting with the specific crystal planes of silver atoms.

[0036] In the synthesis process, polyols are usually used as reducing agents and solvents to generate nanosilver cubes with uniform morphology by reducing the silver ion source material. The addition of polyvinyl pyrrolidone (PVP) is highly dependent on the reaction conditions. By adjusting the mass ratio of the silver ion source material and polyvinyl pyrrolidone (PVP), the synthesis of silver nanowires with different morphologies can be controlled. In the embodiment of the present application, in the step of dissolving the silver ion source material and polyvinyl pyrrolidone (PVP) in a polyol to react and form a first mixed solution, the mass ratio of the silver ion source material and polyvinyl pyrrolidone is 1:0.6~1:1.2, preferably 1:0.8. The mass ratio within this range is conducive to the subsequent formation of a first intermediate product with a diameter of 20nm~50nm. By adjusting the mass ratio of the silver ion source material and polyvinyl pyrrolidone (PVP), the length and diameter ratio of the first intermediate product can be controlled. The mass ratio of the silver ion source material to polyvinyl pyrrolidone can be 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, etc., or a range consisting of any two of the above values, for example, it can be 1:0.6~1:0.8, 1:0.8~1:1.2, 1:0.9~1:1.1, etc.

[0037] In the embodiment of the present application, the diameter of the first intermediate product is 20nm~50nm, that is, the first intermediate product obtained in the first mixed solution is a silver nanowire wrapped with polyvinyl pyrrolidone (PVP) along the length direction with a diameter of 20nm~50nm. Silver nanowires with a diameter within this range are conducive to the subsequent formation of a stable core-shell structure. The diameter of the silver nanowire can be 20nm, 21nm, 25nm, 31nm, 36nm, 38nm, 40nm, 45nm, 50nm, etc., or a range composed of any two of the above values, for example, it can be 20nm~31nm, 31nm~40nm, 40nm~50nm, 25nm~38nm, 36nm~45nm, etc.

[0038] The silver ion source material includes at least one of silver nitrate, silver acetate, silver fluoride and silver perchlorate. The silver nanowires formed by the silver ion source material not only have nano-size effects such as small volume, large specific surface area, good light transmittance and strong flexibility, but also have excellent electrical conductivity, chemical stability, thermal conductivity, antibacterial property, biocompatibility and other chemical and physical properties.

[0039] The molecular weight of polyvinyl pyrrolidone (PVP) ranges from 36000 to 50000. 36000 is preferred. The molecular weight of polyvinyl pyrrolidone (PVP) affects the coating rate of the {100} crystal plane of the silver core. The interaction between polyvinyl pyrrolidone (PVP) with a smaller molecular weight and silver ions is relatively weak, and the diffusion and reaction of silver ions are easier than the interaction between polyvinyl pyrrolidone (PVP) with a larger molecular weight and silver ions. Therefore, when polyvinyl pyrrolidone (PVP) with a smaller molecular weight is used, the silver nanowires elongate faster. At the same time, polyvinyl pyrrolidone (PVP) with a smaller molecular weight has a smaller length-to-length ratio. The molecular weight of polyvinylpyrrolidone (PVP) can be 36000, 38000, 40000, 42000, 45000, 48000, 50000, etc., or a range consisting of any two of the above values, for example, it can be 36000-42000, 42000-48000, 48000-50000, 40000-45000, etc.

[0040] The polyol includes at least one of ethylene glycol, 1,2-propylene glycol or glycerol. The polyol acts as a reducing agent and a solvent at the same time, and generates nanosilver cubes with uniform morphology by reducing the silver ion source material.

[0041] S120: providing a second mixed solution containing a thiol group.

[0042] The step of providing a second mixed solution containing thiol groups includes: adding a thiol compound to an alkaline solution and adjusting the pH value to between 7.0 and 9.0 to obtain a second mixed solution containing thiol groups. The pH value may be 7.0, 7.1, 7.3, 7.5, 7.8, 8.0, 8.1, 8.3, 8.5, 8.8, 9.0, etc., or a range consisting of any two of the above values, for example, 7.0-7.8, 7.8-8.3, 8.3-9.0, 7.3-8.5, etc.

[0043] Wherein, the alkaline solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution.

[0044] The thiol compound includes at least one of thioglycolic acid, mercaptopropionic acid, 2-mercaptopropane, cysteine, mercaptoethylamine, 3-mercapto-1-propylamine, and 4-amino-2-mercaptopyrimidine.

[0045] S130: Mix the first mixed liquid and the second mixed liquid to obtain a third mixed liquid.

[0046] The first mixed solution includes a first intermediate product, which is a silver nanowire wrapped with polyvinyl pyrrolidone (PVP) along the length direction, and the second mixed solution includes a thiol compound. Figure 3, thiol (-SH) was used to modify both ends of the silver nanowires coated with polyvinyl pyrrolidone (PVP).

[0047] The third mixed solution includes a second intermediate product, which is a silver nanowire wrapped with polyvinyl pyrrolidone (PVP) along the length direction and with thiol wrapped at the end.

[0048] Specifically, after the first mixed liquid and the second mixed liquid are mixed, the first mixed liquid includes a first intermediate product, which is a silver nanowire wrapped with polyvinyl pyrrolidone (PVP) along the length direction, and the second mixed liquid contains a thiol compound. The obtained third mixed liquid contains the second intermediate product, which is a silver nanowire wrapped with polyvinyl pyrrolidone (PVP) along the length direction and with thiol wrapped at the end, forming a bridging effect for subsequent steps.

[0049] According to one embodiment of the present application, in the step of mixing the first mixed solution and the second mixed solution to obtain the third mixed solution, the mass ratio of the silver ion source material to the thiol compound in the second mixed solution containing thiol groups is 1:1 to 1:5. The mass ratio within this range is conducive to the generation of the second intermediate product. The mass ratio of the silver ion source material to the thiol compound can be 1:1, 1:1.5, 1:2, 1:2.2, 1:2.5, 1:3.0, 1:3.5, 1:4.0, 1:4.3, 1:4.8, 1:5, etc., or a range consisting of any two of the above values, for example, it can be 1:1 to 1:2.5, 1:2.5 to 1:4.0, 1:4.0 to 1:5, 1:2 to 1:4.8, etc.

[0050] According to an embodiment of the present application, in the step of mixing the first mixed solution and the second mixed solution to obtain the third mixed solution, the stirring time is 30min~90min, preferably, the stirring time is 45-60min. Stir well to form the second intermediate product. The stirring time can be 30min, 35min, 40min, 45min, 48min, 52min, 55min, 60min, 67min, 75min, 81min, 86min, 90min, etc., or a range composed of any two of the above values, for example, 30min~45min, 45min~60min, 67min~81min, 81min~90min, 40min~67min, 60min~86min, etc.

[0051] S140: adding carboxyl-modified titanium dioxide microspheres to the third mixed solution to obtain a fourth mixed solution.

[0052] Specifically, the third mixed solution contains a second intermediate product, which is a silver nanowire wrapped with polyvinyl pyrrolidone (PVP) along the length direction and with thiol groups wrapped at the ends. The titanium dioxide is connected to the titanium dioxide after a polycondensation reaction with the carboxyl groups on the carboxyl-modified titanium dioxide microspheres, thereby forming a third intermediate product.

[0053] The fourth mixed liquid includes the third intermediate product, which is a silver nanowire wrapped with polyvinyl pyrrolidone (PVP) along the length direction and with titanium dioxide wrapped at the end.

[0054] According to one embodiment of the present application, in the step of adding carboxyl-modified titanium dioxide microspheres to the third mixed solution to obtain the fourth mixed solution, the mass ratio of the carboxyl-modified titanium dioxide microspheres to the thiol compound is 1:0.1 to 1:1, preferably, the mass ratio is 1:0.2 to 1:0.6. The mass ratio of the carboxyl-modified titanium dioxide microspheres to the thiol compound within this range can allow the second intermediate product to react fully and avoid exposed silver nanowire ends.

[0055] According to one embodiment of the present application, in the step of adding carboxyl-modified titanium dioxide microspheres to the third mixed solution to obtain the fourth mixed solution, the stirring time is 30min~120min, preferably, the stirring time is 60min~90min. Stir well to form the third intermediate product. The stirring time can be 30min, 35min, 40min, 48min, 55min, 60min, 75min, 86min, 90min, 95min, 110min, 115min, 120min, etc., or a range composed of any two of the above values, for example, 30min~60min, 60minn~90min, 90min~120min, 40min~75min, 48min~95min, 55min~110min, etc.

[0056] S150: The fourth mixed solution is processed to separate the silver nanowires whose ends are coated with titanium dioxide.

[0057] The step of treating the fourth mixed solution to separate the silver nanowires with titanium dioxide wrapped at the ends includes: centrifuging, washing and dispersing the fourth mixed solution. The number of repetitions is more than 5 times, so as to wash away the polyvinyl pyrrolidone (PVP) and the carboxyl-modified titanium dioxide microspheres that have not participated in the reaction.

[0058] S160: Dispersing silver nanowires with titanium dioxide wrapped at the ends into an acrylic acid solution to obtain a conductive ink.

[0059] According to one embodiment of the present application, in the step of dispersing the silver nanowires with titanium dioxide wrapped at the ends into an acrylic acid solution to obtain a conductive ink, the mass fraction of the silver nanowires with titanium dioxide wrapped at the ends in the acrylic acid solution is 0.1% to 10%. The mass ratio within this range has a good consistency, which is conducive to the subsequent formation of a coating film. The mass fraction of the silver nanowires with titanium dioxide wrapped at the ends in the acrylic acid solution can be 0.1%, 0.5%, 1%, 2%, 2.5%, 5%, 5.8%, 6.9%, 8.0%, 9.5%, 10%, etc., or a range consisting of any two of the above values, for example, it can be 0.1% to 2.5%, 2.5% to 8.0%, 8.0% to 10%, 1% to 9.5%, etc.

[0060] It should be noted that the present application also provides a conductive ink, which is prepared according to steps S110 to S160.

[0061] S170: Combined with reference Figure 4 , coating the surface of the transparent substrate with conductive ink and performing surface drying treatment to obtain the first substrate 101 .

[0062] Specifically, a conductive ink containing silver nanowires with titanium dioxide wrapped at the ends is coated onto the surface of an activated transparent substrate.

[0063] According to one embodiment of the present application, in the step of coating the conductive ink on the surface of the transparent substrate and performing a surface drying treatment to obtain the first substrate 101, the thickness of the wet film formed by the conductive ink on the surface of the transparent substrate is 80nm~200nm, and the temperature of the surface drying treatment is 45°C~65°C. Preferably, the temperature of the surface drying treatment is 50°C~60°C.

[0064] Specifically, after the silver nanowire conductive ink is laid on the surface of the transparent substrate, a layer of silver nanowire ink is formed, and the silver nanowire ink layer is surface dried at a low temperature, and the temperature does not exceed 65°C to evaporate the relevant solvent. At this time, the silver nanowires are loosely overlapped with each other, and the overlap is separated by titanium dioxide wrapped at the end. Since the silver nanowires with titanium dioxide wrapped at the ends in the film layer are only in a state of surface drying but not completely solidified, the overlap state of the silver nanowires is not finalized, which provides the possibility for subsequent further processing and microscopic movement of the silver nanowires, changes in the overlap tightness, etc.

[0065] The thickness of the wet film can be 80nm, 85nm, 96nm, 100nm, 110nm, 120nm, 135nm, 155nm, 164nm, 188nm, 195nm, 200nm, etc., or a range consisting of any two of the above values, for example, it can be 80nm~100nm, 100nm~135nm, 135nm~164nm, 164nm~200nm, 96nm~110nm, 120nm~188nm, 164nm~295nm, etc.

[0066] The temperature of the surface drying treatment is 45°C, 48°C, 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, etc., or a range consisting of any two of the above values, for example, it can be 45°C~52°C, 52°C~60°C, 60°C~65°C, 48°C~58°C, 50°C~60°C, etc.

[0067] S180 : performing a hot pressing process on a preset area of ​​the first substrate 101 to obtain a conductive area 102 .

[0068] In step S170, the conductive ink coated on the first substrate 101 is a silver nanowire with titanium dioxide wrapped at the end, the silver nanowire is a core structure, and the titanium dioxide is a shell structure, forming a silver nanowire core-shell composite material, and its core-shell structure makes it impossible for the silver nanowires to be built and cannot be conductive. In this step, a constant temperature welding binding machine is used to perform hot pressing treatment on the preset area of ​​the first substrate 101 to destroy the core-shell structure. Under high temperature and high pressure, the shell structure of titanium dioxide is broken to expose the silver nanowires. The silver nanowires move microscopically until the silver nanowires are closely overlapped with each other. The electrons between the silver nanowires can be completely conductive through the electron tunneling effect, making the film layer in this area conductive, thereby forming a conductive area 102. The silver nanowire core-shell composite material outside the preset area (i.e., the non-conductive area 103) is not subjected to hot pressing treatment, and the core-shell structure is not broken, so it is non-conductive.

[0069] According to an embodiment of the present application, in the step of performing a hot pressing treatment on a preset area of ​​the first substrate 101 to obtain the conductive area 102, the temperature of the hot pressing treatment is 160°C to 220°C and the pressure is 0.2MPa to 1MPa. The high temperature and high pressure within this range are conducive to the rupture of the core-shell structure of the silver nanowires in the conductive ink, thereby forming the conductive area 102.

[0070] The high temperature is 160°C, 165°C, 170°C, 176°C, 184°C, 188°C, 195°C, 200°C, 202°C, 205°C, 210°C, 215°C, 220°C, etc., or a range consisting of any two of the above values, for example, it can be 160°C~184°C, 184°C~200°C, 200°C~220°C, 170°C~195°C, 176°C~195°C, etc.

[0071] The high pressure is 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa, 0.9MPa, 1MPa, etc., or a range consisting of any two of the above values, for example, it can be 0.2MPa~0.5MPa, 0.5MPa~0.7MPa, 0.7MPa~0.1MPa, 0.4MPa~0.8MPa, etc.

[0072] S190 : baking and curing the area outside the conductive area to obtain the touch conductive film 104 .

[0073] The high temperature and high pressure in step S180 have completely solidified the tight overlap mode of the silver nanowires in the preset area, so that the film layer is little affected by the baking and curing in this step S190, and the silver nanowires in the conductive area 102 are still tightly overlapped and completely conductive. The area outside the conductive area is baked and cured, that is, the insulating area (that is, the non-conductive area 103) is baked and cured, and the baking temperature and baking pressure are lower than the temperature and pressure in step S180. The silver nanowires in this area still maintain the core-shell structure with titanium dioxide at the end, and the wires are still separated by titanium dioxide. It is difficult for electrons to transmit and the insulation is good. Therefore, it is difficult for electrons to conduct between the silver nanowires separated by the core-shell structure, and the film layer in this area is not conductive and has good insulation.

[0074] According to an embodiment of the present application, in the step of baking and curing the area outside the conductive area to obtain the touch conductive film, the baking temperature is 100° C. to 150° C., preferably 120° C. to 140° C. The baking time is 30 min to 150 min, preferably 60 min to 90 min.

[0075] The baking temperature is 100°C, 105°C, 110°C, 120°C, 135°C, 140°C, 146°C, 150°C, etc., or a range consisting of any two of the above values. For example, it can be 100°C~120°C, 120°C~140°C, 140°C~150°C, 110°C~146°C, etc.

[0076] The baking time is 30 min, 55 min, 60 minn, 68 min, 78 min, 90 min, 95 min, 110 min, 135 min, 142 min, 150 min, etc., or a range consisting of any two of the above values, for example, it can be 30 min~60 min, 60 minn~90 min, 90 min~110 min, 110 min~150 min, 55 min~95 min, 68 min~135 min, etc.

[0077] A second aspect of an embodiment of the present application provides a touch conductive film 104 prepared by the above-mentioned touch conductive film preparation method; the touch conductive film 104 includes a silver nanowire core-shell composite material, and the silver nanowire core-shell composite material includes silver nanowires with ends wrapped or partially wrapped with titanium dioxide.

[0078] The present application directly coats the conductive ink prepared by the method of the present application on the surface of a transparent substrate. After the surface is dried, the preset area is subjected to a hot pressing treatment, and the core-shell structure of the silver nanowire core-shell composite material that needs to be conductive is broken by high temperature and high pressure, thereby forming a conductive area 102, i.e., a touch electrode. The non-conductive area is directly baked and cured at a relatively low temperature to form an insulating area. The touch electrode and the non-conductive area 103 together constitute a touch conductive film 104. The present application can obtain a touch conductive film 104 by a one-step molding method using a wet process, which has high preparation efficiency, simple preparation process, high reliability, and low cost.

[0079] A third aspect of the present application embodiment provides an electronic device 10, Figure 4 The electronic device 10 includes a touch component 105 , and the touch component 105 includes the touch conductive film 104 as described above.

[0080] The electronic device 10 may be a mobile phone, a computer, etc. with a touch screen.

[0081] The fourth aspect of the embodiment of the present application provides a conductive ink, which includes an acrylic solution in which silver nanowires with titanium dioxide wrapped at the ends are dispersed. Specifically, the acrylic solution in which silver nanowires with titanium dioxide wrapped at the ends are dispersed is applied to the surface of a transparent substrate, and a surface drying treatment is performed to obtain a first substrate 101; a hot pressing treatment is performed on a preset area of ​​the first substrate 101 to obtain a conductive area 102; and the area outside the conductive area is baked and cured to obtain a touch conductive film 104. The embodiment of the present application can obtain the touch conductive film 104 by one-step molding through a wet process, which has high preparation efficiency, simple preparation process, high reliability and low cost.

[0082] A fifth aspect of an embodiment of the present application provides a method for preparing a conductive ink, comprising dissolving a silver ion source material and polyvinyl pyrrolidone (PVP) in a polyol to react and form a first mixed solution; providing a second mixed solution containing a thiol group; mixing the first mixed solution and the second mixed solution to obtain a third mixed solution; adding carboxyl-modified titanium dioxide microspheres to the third mixed solution to obtain a fourth mixed solution; treating the fourth mixed solution to separate silver nanowires with titanium dioxide wrapped at the ends; and dispersing the silver nanowires with titanium dioxide wrapped at the ends in an acrylic acid solution to obtain a conductive ink.

[0083] Specifically, the conductive ink prepared by the method of this embodiment contains silver nanowires with titanium dioxide wrapped at the ends. The conductive ink is applied to the surface of a transparent substrate and subjected to a surface drying treatment to obtain a first substrate. The surface drying temperature does not exceed 65°C to evaporate the relevant solvent. At this time, the silver nanowires are loosely overlapped with each other, and the overlaps are separated by titanium dioxide wrapped at the ends. Since the silver nanowires with titanium dioxide wrapped at the ends in the film layer are only in a surface drying but not completely solidified state, the overlapping state of the silver nanowires is not finalized, which provides the possibility for subsequent further processing and microscopic movement of the silver nanowires, changes in the overlap tightness, etc. Among them, the silver nanowires are core structures, and titanium dioxide is a shell structure, forming a silver nanowire core-shell composite material, and its core-shell structure makes it impossible to build between the silver nanowires and conduct electricity. Subsequently, the preset area of ​​the first substrate is subjected to hot pressing treatment to destroy the core-shell structure. Under high temperature and high pressure, the shell structure of titanium dioxide is broken to expose the silver nanowires. The silver nanowires move microscopically until the silver nanowires are closely overlapped with each other. The electrons between the silver nanowires can be completely conductive through the electron tunneling effect, making the film layer in this area conductive, thereby forming a conductive area. The silver nanowire core-shell composite material outside the preset area is not subjected to hot pressing treatment, and the core-shell structure is not broken, so it is non-conductive. The area outside the conductive area is baked and cured, and the baking temperature and baking pressure are lower than the temperature and pressure when the conductive area is prepared. The silver nanowires in this area still maintain the core-shell structure with titanium dioxide at the end, and the wires are still separated by titanium dioxide. It is difficult for electrons to transmit and the insulation is good. Therefore, it is difficult for electrons to conduct between the silver nanowires separated by the core-shell structure, and the film layer in this area is non-conductive and has good insulation.

[0084] The embodiment of the present application can obtain the touch conductive film by one-step molding through a wet process, which has high preparation efficiency, simple preparation process, high reliability and low cost.

[0085] The above description is only an embodiment of the present application and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A method for preparing a touch conductive film, characterized in that: include: Dissolving the silver ion source material and polyvinyl pyrrolidone in polyol to react to form a first mixed solution; providing a second mixed solution containing a thiol group; mixing the first mixed liquid and the second mixed liquid to obtain a third mixed liquid; adding carboxyl-modified titanium dioxide microspheres to the third mixed solution to obtain a fourth mixed solution; Treating the fourth mixed solution to separate the silver nanowires with ends coated with titanium dioxide; Dispersing the silver nanowires with titanium dioxide wrapped at the ends into an acrylic acid solution to obtain a conductive ink; The conductive ink is coated on the surface of a transparent substrate and subjected to surface drying treatment to obtain a first substrate; Performing heat pressing treatment on a preset area of ​​the first substrate to obtain a conductive area; The area outside the conductive area is baked and cured to obtain a touch conductive film.

2. The method for preparing a touch conductive film according to claim 1, wherein: The first mixed solution includes a first intermediate product, which is a silver nanowire wrapped with polyvinyl pyrrolidone along the length direction, and the diameter of the first intermediate product is 20nm~50nm.

3. The method for preparing a touch conductive film according to claim 1, wherein: In the step of dissolving the silver ion source material and polyvinyl pyrrolidone in a polyol to react and form a first mixed solution, at least one of the following conditions is met: (1) The mass ratio of the silver ion source material to the polyvinyl pyrrolidone is 1:0.6 to 1:1.2; (2) the silver ion source material comprises at least one of silver nitrate, silver acetate, silver fluoride and silver perchlorate; (3) The molecular weight of the polyvinyl pyrrolidone is in the range of 36000 to 50000; (4) The polyol includes at least one of ethylene glycol, 1,2-propylene glycol or glycerol.

4. The method for preparing a touch conductive film according to claim 1, wherein: The step of providing a second mixed solution containing thiol groups comprises: A thiol compound is added to the alkaline solution and the pH value is adjusted to be between 7.0 and 9.0 to obtain a second mixed solution containing thiol groups.

5. The method for preparing a touch conductive film according to claim 4, wherein: The alkaline solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution; And / or, the thiol compound includes at least one of thioglycolic acid, mercaptopropionic acid, 2-mercaptopropane, cysteine, mercaptoethylamine, 3-mercapto-1-propylamine, and 4-amino-2-mercaptopyrimidine.

6. The method for preparing a touch conductive film according to claim 1, wherein: In the step of mixing the first mixed solution and the second mixed solution to obtain a third mixed solution, the mass ratio of the silver ion source material to the thiol compound in the second mixed solution containing thiol groups is 1:1 to 1:

5.

7. The method for preparing a touch conductive film according to claim 1, wherein: In the step of mixing the first mixed solution and the second mixed solution to obtain the third mixed solution, the stirring time is 30 min to 90 min; In the step of adding carboxyl-modified titanium dioxide microspheres to the third mixed solution to obtain a fourth mixed solution, the stirring time is 30 min to 120 min; The step of treating the fourth mixed solution to separate the silver nanowires with ends wrapped with titanium dioxide comprises: centrifuging, washing and dispersing the fourth mixed solution.

8. The method for preparing a touch conductive film according to claim 1, wherein: In the step of adding carboxyl-modified titanium dioxide microspheres to the third mixed solution to obtain the fourth mixed solution, the mass ratio of the carboxyl-modified titanium dioxide microspheres to the thiol compounds in the second mixed solution containing thiol groups is 1:0.1 to 1:

1.

9. The method for preparing a touch conductive film according to claim 1, wherein: In the step of dispersing the silver nanowires with titanium dioxide wrapped at the ends into an acrylic acid solution to obtain a conductive ink, the mass of the silver nanowires with titanium dioxide wrapped at the ends is 0.1% to 10% of the mass of the acrylic acid solution.

10. The method for preparing a touch conductive film according to claim 1, wherein: In the step of coating the conductive ink on the surface of a transparent substrate and performing a surface drying treatment to obtain a first substrate, the thickness of a wet film formed by the conductive ink on the surface of the transparent substrate is 80 nm to 200 nm, and the temperature of the surface drying treatment is 45° C. to 65° C.

11. The method for preparing a touch conductive film according to claim 1, wherein: In the step of performing a hot pressing treatment on a preset area of ​​the first substrate to obtain a conductive area, the temperature of the hot pressing treatment is 160° C. to 220° C. and the pressure is 0.2 MPa to 1 MPa.

12. The method for preparing a touch conductive film according to claim 1, wherein: In the step of baking and curing the area outside the conductive area to obtain the touch conductive film, the baking temperature is 100° C. to 150° C.

13. A touch conductive film, characterized in that: Prepared according to the method for preparing a touch conductive film according to any one of claims 1 to 12; The touch conductive film comprises a silver nanowire core-shell composite material, and the silver nanowire core-shell composite material comprises silver nanowires with ends wrapped with titanium dioxide or with parts of ends wrapped with titanium dioxide.

14. An electronic device, characterized in that: The electronic device comprises a touch control component, and the touch control component comprises the touch control conductive film as claimed in claim 13.

15. A method for preparing a conductive ink, characterized in that: Dissolving the silver ion source material and polyvinyl pyrrolidone (PVP) in polyol to form a first mixed solution; providing a second mixed solution containing a thiol group; mixing the first mixed liquid and the second mixed liquid to obtain a third mixed liquid; adding carboxyl-modified titanium dioxide microspheres to the third mixed solution to obtain a fourth mixed solution; Treating the fourth mixed solution to separate the silver nanowires with ends coated with titanium dioxide; The silver nanowires with titanium dioxide wrapped at the ends are dispersed in an acrylic acid solution to obtain the conductive ink.

Citation Information

Patent Citations

  • Production method of silver nanowire transparent conductive film

    CN104992752A